Recent Publications (Quarterly Journal of Economics, 1937)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 52, Issue 1, November 1937, Pages 186–190, https://doi.org/10.1093/qje/52.1.186 Published: 01 November 1937